The Role of Mentoring in Shaping Educational Aspirations: A Theory of Planned Behavior Study of Hmong Students in Vietnam - Thanh-Truc, Dang (INTI International University, 2024)
This study examines the influence of mentorship on the desire to pursue higher education among Hmong ethnic minority students aged 12-15 in Lao Cai Province, Vietnam. Utilizing the Theory of Planned Behavior as a theoretical framework, the research investigates how cross-ethnic mentorship between Kinh majority mentors and Hmong minority mentees affects students' educational aspirations, using the Phieu Linh Educational Summer Camp as a case study. The study employed a quantitative approach, collecting survey data from 75 Hmong students participating in the summer camp. Five key aspects of mentorship were analyzed: quality, educational accessibility, clear educational outcomes, self-awareness, and cultural identity support, in relation to the components of the Theory of Planned Behavior. Results indicate that all mentorship aspects positively correlate with students' educational desires, with mentorship quality emerging as the strongest factor. Family support and household income were also found to significantly influence educational aspirations. The study reveals that culturally responsive mentorship can play a crucial role in shaping attitudes, subjective norms, and perceived behavioral control related to pursuing higher education among ethnic minority youth. This research contributes to the understanding of effective strategies for promoting educational equity in Vietnam's multicultural context. It offers insights for designing targeted interventions and policies to support the educational aspirations of ethnic minority students, potentially contributing to narrowing educational gaps among ethnic groups in Vietnam.